2019
DOI: 10.21608/aasj.2019.16416.1009
|View full text |Cite
|
Sign up to set email alerts
|

Follicular diameters and progesterone level in Egyptian ewe lambs using flushing and some hormonal treatments

Abstract: The objectives of this study were to explore the influence of flushing and hormonal treatments on the follicular diameters and progesterone level during estrus and pregnancy rate in Egyptian ewe lambs. This study was carried out on 25 ewe lambs clinically healthy (body weight 27-33 Kg. and age 8-12 months). The animals divided into 5 groups; group 1: served as a control, group 2: received vaginal sponges impregnated medroxyprogesterone acetate (MAP) for 14 days, group 3: received vaginal sponges impregnated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Cleavage, morula, and blastocyst rates were increased in the media containing 50 μM of βME rather than those of control which agreed with Sadeesh et al ( 20 ), who stated that supplementation of antioxidants such as βME to the culture medium enhanced the antioxidant systems within the embryo and stimulated the embryonic development. Thus, the oocyte developmental competence could be improved by increasing the antioxidant capacity of the oocytes during maturation in vitro ( 36 , 37 ). The present results are supported by Sidi et al ( 18 ) studies which reported that low molecular weight thiol-compounds like the cysteamine or βME could stimulate the synthesis of oocyte GSH.…”
Section: Discussionmentioning
confidence: 99%
“…Cleavage, morula, and blastocyst rates were increased in the media containing 50 μM of βME rather than those of control which agreed with Sadeesh et al ( 20 ), who stated that supplementation of antioxidants such as βME to the culture medium enhanced the antioxidant systems within the embryo and stimulated the embryonic development. Thus, the oocyte developmental competence could be improved by increasing the antioxidant capacity of the oocytes during maturation in vitro ( 36 , 37 ). The present results are supported by Sidi et al ( 18 ) studies which reported that low molecular weight thiol-compounds like the cysteamine or βME could stimulate the synthesis of oocyte GSH.…”
Section: Discussionmentioning
confidence: 99%
“…C. barbara can act as an intermediate host for Protostrongylus rufescens (sheep lungworm) (Herbert, 2010). Introductions of nonindigenous species can result in substantial ecological, agricultural, medical, and economic problems and extirpation of native fauna (Ali et al, 2019;Rahel, 2002). Several studies indicated that this species was found in many Delta Governorates, northern Egypt (Akra 2001;Ali, 2017;Eshra, 2013;Gazzy et al, 2019;Mohammed 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Propolis contains vitamins B1, B2, and B6, as well as minerals magnesium, calcium, potassium, iron, and a few enzymes; succinic dehydrogenase, glucose-6-phosphatase, adenosine triphosphates, and acid phosphatase (Lotfy, 2006). The phenolic compounds contribute to the antioxidant, antimicrobial, antiviral, anti-inflammatory, antifungal, wound healing and cardio protective functions (Huang et al, 2014;Ali et al, 2019;Hussein et al, 2022).…”
mentioning
confidence: 99%